Social Marking in Memory Entrepreneurship: The Battle Over Zapata’s Legacy - Schafer, Tyler S.; Dickens, David R. (Qualitative Sociology Review, 2016)
Disputes over historical representations often revolve around competing narratives about the past, but the processes through which these narratives are constructed are often neglected. In this paper, we extend the concept of collective memory using Brekhus’ notion of social marking to investigate the creation and maintenance of collective representations of the Mexican revolutionary Emiliano Zapata. We analyze the claims made in speeches and communiqués produced by two opposing groups—the Mexican government and the Zapatista movement—in a decades-long dispute over land and indigenous rights. Moreover, we argue that processes of social marking can further explain the selective nature of collective memory, that is, how certain parts of the past are remembered and emphasized while others are de-emphasized and forgotten. Also, in our analysis of social marking, we identify a naturalization process that is utilized by actors in mnemonic battles to recast their constructed representations of the past as natural, pure, and true. We close with a discussion of how understanding the naturalization process as outlined here can shed light on current political and historical disputes.